Evaluating the Implementation of a Mental Health Referral Service “Connect to Wellbeing”: A Quality Improvement Approach - Onnis, Leigh-ann; Kinchin, Irina; Pryce, Josephine; Ennals, Priscilla; Petrucci, Joe; Tsey, Komla (Frontiers in Public Health, 2020)
There is increasing demand for mental health services to be accessible to diverse populations in flexible, yet, cost-effective ways. This article presents the findings from a study that evaluated the process of implementing Connect to Wellbeing (CTW), a new mental health intake, assessment and referral service in regional Australia, to determine how well it improved access to services, and to identify potential measures that could be used to evaluate value for money. The study used a hybrid study design to conduct a process evaluation to better understand: the process of implementing CTW; and the barriers and factors enabling implementation of CTW. In addition, to better understand how to measure the cost-effectiveness of such services, the hybrid study design included an assessment of potential outcome measures suitable for ascertaining both the effectiveness of CTW in client health outcomes, and conducting a value for money analysis. The process evaluation found evidence that by improving processes, and removing waitlists CTW had created an opportunity to broadened the scope and type of psychological services offered which improved accessibility. The assessment of potential outcome measures provided insight into suitable measures for future evaluation into service effectiveness, client health outcomes and value for money.